SHEVCHENKO AS “ABSOLUTE TOPICALITY”: NATIONAL ONTOLOGY OF THE UKRAINIAN SIXTIERS - Tarnashynska, L. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
D. Chyzhevsky’s thesis – to look for Shevchenko value in a aesthetic area – became a defining one in research of national ontology of Ukrainian 60’s. The article considers Shevchenko’s word projections in the art of 60’s literaturt generation.